What chemical reaction dominates the CO2 and O2 in-situ uranium leaching? Insights from a three-dimensional multicomponent reactive transport model at the field scale - Qiu, Wenjie; Yang, Yun; Song, Jian; Que, Weimin; Liu, Zhengbang; Weng, Haicheng; Wu, Jianfeng; Wu, Jichun (Applied geochemistry, 2023)
The complex behavior of uranium in recovery is mostly driven by water-rock interactions following lixiviant injection into ore-bearing aquifers. Significant challenges exist in exploring the geochemical processes responsible for uranium release and mobilization. Herein this study provides an illustration of a ten-year field scale CO2 and O2in-situ leaching (ISL) process at a typical sandstone-hosted uranium deposit in northern China. We also conducte a three-dimensional (3-D) multicomponent reactive transport model to assess the effects of potential chemical reactions on uranium recovery, in particular, to focus on the role of sulfide mineral pyrite (FeS2). Numerical simulations are performed considering three potential ISL reaction pathways to determine the relative contributions to uranium release, and the results indicate that bicarbonate promotes the oxidative dissolution of uranium-bearing minerals and further accelerates the uranium leaching in a neutral geochemical system. Moreover, the presence of FeS2 exerts a strong competitive role in the uranium-bearing mineral dissolution by increasing oxygen consumption, favoring the formation of iron oxyhydroxide, and therefore causing an associated decrease in uranium recovery rates. The simulation model demonstrates that dissolution of carbonate neutralizes acidic water generated from pyrite oxidation and aqueous CO2 dissociation. In addition, the cation concentrations (i.e., Ca and Mg) are increasing in the pregnant solutions, showing that the recycling of lixiviants and kinetic dissolution of carbonate generates a larger number of dissolved Ca and Mg and inevitably triggers the secondary dolomite mineral precipitation. The findings improve our fundamental understanding of the geochemical processes in a long-term uranium ISL system and provide important environmental implications for the optimal design of uranium recovery, remediation, and risk exposure assessment. [Display omitted] •Process-based reactive transport modeling is developed for clarifying uranium recovery processes.•Assessment of multi-reaction showed dissolved oxygen dominates the CO2 and O2 in-situ leaching of uranium.•Co-existing pyrite plays a significant role in uranium mobilization.•Chemical clogging induced by secondary mineral precipitates is non-ignorable.